2017
DOI: 10.1016/j.heares.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

An overview of cochlear implant electrode array designs

Abstract: Cochlear implant electrode arrays are designed with specific characteristics that allow for the preservation of intra-cochlear structures during the insertion process, as well as during explantation. Straight lateral wall (LW) electrode arrays and pre-curved modiolar hugging (MH) electrode arrays are the two types that are commercially available. Although there is a third type of electrode array called the mid-scala (MS), which is positioned in the middle of the scala tympani (ST), and is usually considered as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
196
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(209 citation statements)
references
References 92 publications
7
196
1
5
Order By: Relevance
“…Current CI electrodes are designed as either "precurved" or "straight". Precurved electrodes are designed to curl around the medial wall and to assume a midscalar or perimodiolar position close to the modiolus, while straight electrodes assume a more lateral position, following the lateral wall of the cochlea [1]. Several studies have shown that perimodiolar electrodes, compared to lateral wall electrodes, lead to lower stimulation thresholds and reduced spread of excitation; stimulating a more specific, tonotopic region of spiral ganglion cells [2][3][4][5][6][7].…”
Section: Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…Current CI electrodes are designed as either "precurved" or "straight". Precurved electrodes are designed to curl around the medial wall and to assume a midscalar or perimodiolar position close to the modiolus, while straight electrodes assume a more lateral position, following the lateral wall of the cochlea [1]. Several studies have shown that perimodiolar electrodes, compared to lateral wall electrodes, lead to lower stimulation thresholds and reduced spread of excitation; stimulating a more specific, tonotopic region of spiral ganglion cells [2][3][4][5][6][7].…”
Section: Rationalementioning
confidence: 99%
“…Several studies have shown that perimodiolar electrodes, compared to lateral wall electrodes, lead to lower stimulation thresholds and reduced spread of excitation; stimulating a more specific, tonotopic region of spiral ganglion cells [2][3][4][5][6][7]. On the other hand, conventional perimodiolar electrodes translocate to the scala vestibuli (SV) at a higher rate compared to lateral wall electrodes [1,8,9]. These translocations are shown to be traumatic and are associated with loss of residual hearing and poorer speech perception [8,10,11].…”
Section: Rationalementioning
confidence: 99%
“…In this technique, a magnet attached to the tip of the electrode array is guided in the cochlear turns via an external magnetic field (see Fig. 1) [4]. After surgery, the magnet must be detached from the electrode array and removed from the cochlea to avoid potential medical complications arising when the patient is exposed to a strong magnetic field [5].…”
Section: Introductionmentioning
confidence: 99%
“…3D uncoiled model of the cochlea with inserted electrode array and magnet. The electrode array model is made by MED-EL[4].…”
mentioning
confidence: 99%
“…However, due to the wide spread of the electrical current from each of the 12-24 eCI contacts (depending on manufacturer 5 ), signals containing information of a given frequency band activate a large fraction of the tonotopically ordered SGNs. This results in limited spectral resolution of sound coding with typically less than ten perceptually independently stimulation channels [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%